Algorithms for Game AI - Wenxin Li; Haifeng Zhang (Algorithms, 2025)
Games have long been benchmarks for AI algorithms and, with the boost of computational power and the application of new algorithms, AI systems have achieved superhuman performance in games for which it was once thought that they could only be mastered by humans due to their high complexity [...]